Handbook of Life Course Health Development - Halfon, Neal; Forrest, Christopher B.; Lerner, Richard M.; Faustman, Elaine M. (Springer Nature, 2018)
Health development science; Developmental origins of chronic illnesses; Community; Diabetes; Autism; Obesity; Nutrition; Health disparities across the lifespan; Fetal programming